If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + -6t = 4 + -4t Solving 18 + -6t = 4 + -4t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '4t' to each side of the equation. 18 + -6t + 4t = 4 + -4t + 4t Combine like terms: -6t + 4t = -2t 18 + -2t = 4 + -4t + 4t Combine like terms: -4t + 4t = 0 18 + -2t = 4 + 0 18 + -2t = 4 Add '-18' to each side of the equation. 18 + -18 + -2t = 4 + -18 Combine like terms: 18 + -18 = 0 0 + -2t = 4 + -18 -2t = 4 + -18 Combine like terms: 4 + -18 = -14 -2t = -14 Divide each side by '-2'. t = 7 Simplifying t = 7
| -47-2x=9+10x | | 2/3x-5=17 | | -9-5b=11 | | y=21+4 | | 2-(a+6)=-22 | | 2/9x+2=10x-4 | | -7=-7r | | k^2-5k-16=8 | | 3/4v-6=-1/4v+5 | | 3y-7+y+47=7y+40-5y | | x^2+2x=8x | | 8(3)-4y=0 | | -6/x=10/8 | | -6x+8=-8x+4 | | 8x-4y=0 | | -6=k+3 | | x^2=1.96 | | 4x^2-8=-13x | | 2w+2(3w-5)= | | 7x-4=8x+1 | | 17=29-x | | -3(5n-4)+2n= | | 4c^2=-5c+3c^2-2 | | 4(x-2)-3x=5(2-x) | | -13=-17+a | | x+(5x+6)=60 | | 7-8(a+2)=9+a | | 5m^2+27m+10=0 | | -32x=16-x^2 | | 5x+11-3x+13=-2 | | 8a+10=9+a | | 1/3y=-5 |